2002
DOI: 10.1029/2000jd000140
|View full text |Cite
|
Sign up to set email alerts
|

Regional levels of ozone in the troposphere over eastern Mediterranean

Abstract: [1] During the last 5 years, information on the regional tropospheric ozone levels over the eastern Mediterranean has become available but was confined to measurements at ground level. Here available information is expanded with measurements at two more rural ground level sites spanning 8°latitude, ozonesonde ascents, lidar observations, ship cruises, and aircraft flights. During wintertime the ozone monthly values are 10-20 ppbv higher than values at other European sites, while during summertime the values ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 35 publications
3
51
0
6
Order By: Relevance
“…Similar results were obtained during short-term intensive measuring campaigns over the Aegean Sea (MEDCAPHOT-TRACE campaign in summer 1994, PAUR I campaign in summer 1996, PAUR II campaign in summer 1999, MINOS campaign in summer 2001) using aircraft and surface measurements PAUR report, 1998;Kourtidis et al, 2002;Kouvarakis et al, 2002;Traub et al, 2003;Roelofs et al, 2003). Recent continuous 3-year (1997-1999) measurements in the island of Crete agree also with the measurements presented above (Kouvarakis et al, 2000).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results were obtained during short-term intensive measuring campaigns over the Aegean Sea (MEDCAPHOT-TRACE campaign in summer 1994, PAUR I campaign in summer 1996, PAUR II campaign in summer 1999, MINOS campaign in summer 2001) using aircraft and surface measurements PAUR report, 1998;Kourtidis et al, 2002;Kouvarakis et al, 2002;Traub et al, 2003;Roelofs et al, 2003). Recent continuous 3-year (1997-1999) measurements in the island of Crete agree also with the measurements presented above (Kouvarakis et al, 2000).…”
Section: Discussionsupporting
confidence: 84%
“…High surface ozone values have been already reported at western and central Mediterranean sites in Italy and Spain (Millan et al, 1992;Bonasoni et al, 2000). Concerning the eastern Mediterranean, several intensive shortterm measurements including aircraft flights have been carried out in Greece, around the urban area of Athens and over the Aegean Sea during the past decade, which recorded high surface ozone values (Kallos, 1995;Ziomas, 1998;PAUR report, 1998;Kourtidis et al, 2002;Kouvarakis et al, 2002;Traub et al, 2003;Roelofs et al, 2003). In Greece, few systematic rural ozone measurements outside the greater Athens area have been published so far covering time-periods of several months to 2-3 years (Kourtidis et al, 1996;Glavas, 1999;Kouvarakis et al, 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Varotsos et al, 1993;Kalabokas et al, 2000;Kourtidis et al, 2002;Kouvarakis et al, 2002;Zerefos et al, 2002;Lelieveld et al, 2002;Roelofs et al, 2003;Kalabokas and Repapis, 2004). Such high summer levels are a general characteristic of the ozone vertical profiles in the region.…”
Section: Introductionmentioning
confidence: 93%
“…They identified transport from the European continent as the main mechanism controlling the O 3 levels in the EM, especially during summer when O 3 reaches a July maximum of 58 ± 10 ppbv. Moreover, on a larger regional scale, Kourtidis et al (2002) used ozonesonde ascents, lidar observations, ship cruises, and aircraft flights to show that south and southwestern synoptic flows associated with Saharan dust events result in lower O 3 above the planetary boundary layer by 20-35 ppbv, as compared to northerly flows, which transport air from continental Europe. Based on 16 years of O 3 concentrations measured at the EMEP Agia Marina Xyliatou rural background station in Cyprus and three other remote marine sites over the western, central, and eastern parts of the island, Kleanthous et al (2014) have shown that local precursors contribute to only about 6 % (∼ 3 ppbv) of the observed O 3 .…”
Section: Processes Controlling O 3 Formationmentioning
confidence: 99%